Comment: The Social Neuroendocrinology Example: Incorporating Culture Resolves Biobehavioral Evolutionary Paradoxes. (July 2014) - van Anders, Sari M.
The target meta-analysis (Wood, Kressel, Joshi, & Louie, 2014) raises a number of red flags for research on menstrual shifts in women's psychology. In this commentary, I particularly address one: the near-absent attention to sociocultural forces in this body of work. I use social neuroendocrinology as one example of a research paradigm that integrates both evolution and socialization into studies of human behavior. I argue that incorporating attention to social constructions actually provides clearer answers to evolutionary questions and also fills the biobehavioral comparative mandate by seriously attending to human specificities alongside cross-species generalities. I close by noting that human bodies simultaneously reflect evolved and sociocultural forces, an understanding that undergirds contemporary biobehavioral research.